Fine epitope mapping of glycoprotein Gn in Guertu virus - Zhang, Jingyuan; Moming, Abulimiti; Yue, Xihong; Shen, Shu; Liu, Dongliang; Xu, Wan-xiang; Wang, Chen; Ding, Juntao; Li, Yijie; Deng, Fei; Zhang, Yujiang; Sun, Surong (PloS one, 2019)
Guertu virus (GTV) is a tick-borne phleboviruses (TBPVs) which belongs to the genus Banyangvirus in the family of Phenuiviridae. In vitro and in vivo studies of GTV demonstrated that it was able to infect animal and human cell lines and could cause pathological lesions in mice. Glycoproteins (GP, including Gn and Gc) on the surface of Guertu virus (GTV) could bind to receptors on host cells and induce protective immunity in the host, but knowledge is now lacking on the information of B cell epitopes (BCEs) present on GTV-GP protein. The aim of this study was to identify all BCEs on Gn of the GTV DXM strain using rabbit pAbs against GTV-Gn. Seven fine BCEs and two antigenic peptides (APs) from nine reactive 16mer-peptides were identified, which are EGn1 (2PIICEGLTHS11), EGn2 (135CSQDSGT141), EGn3 (165IP EDVF170), EGn4 (169VFQEL K174), EGn5 (187IDGILFN193), EGn6 (223QTKWIQ228), EGn7 (237CHKDGIGPC245), AP-8 (299GVRVRPKCYGFSRMMA314) and AP-9 (355CASH FCSSAESGKKNT370), of which six of mapped BCEs were recognized by the IgG-positive sheep serum obtained from sheep GTV-infected naturally. Multiple sequence alignments (MSA) based on each mapped BCE motif identified that the most of identified BCEs and APs are highly conserved among 10 SFTSV strains from different countries and lineages that share relatively close evolutionary relationships with GTV. The fine epitope mapping of the GTV-Gn would provide basic data with which to explore the GTV-Gn antigen structure and pathogenic mechanisms, and it could lay the foundation for the design and development of a GTV multi-epitope peptide vaccine and detection antigen.